Managing workplace bullying in New Zealand: Perspectives from occupational health and safety practitioners. (21st May 2014) - Catley, Bevan; Bentley, Tim; Forsyth, Darryl; Cooper-Thomas, Helena; Gardner, Dianne; O'Driscoll, Michael; Trenberth, Linda
Abstract Research into workplace bullying has only recently begun to investigate preventative measures. This paper continues that emphasis by examining the management of bullying in a sample of New Zealand organisations. In this study, the survey results from 252 occupational health and safety practitioners were analysed to examine how bullying is understood and managed, along with factors that predict preventative efforts. Results indicate that bullying was perceived to impact significantly on organisations, although the organisations had limited preventative measures in place. The findings confirm the importance of leadership and the establishment of an effective bully-free environment as preventative measures.